2020
DOI: 10.3390/polym12092111
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Extrusion Screw Speed and Plasticizer Proportions on the Rheological, Thermal, Mechanical, Morphological and Superficial Properties of PLA

Abstract: One of the critical processing parameters—the speed of the extrusion process for plasticized poly (lactic acid) (PLA)—was investigated in the presence of acetyl tributyl citrate (ATBC) as plasticizer. The mixtures were obtained by varying the content of plasticizer (ATBC, 10–30% by weight), using a twin screw extruder as a processing medium for which a temperature profile with peak was established that ended at 160 °C, two mixing zones and different screw rotation speeds (60 and 150 rpm). To evaluate the therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 48 publications
(103 reference statements)
1
30
1
Order By: Relevance
“…CAPs derivatives are widely used as eco‐friendly plasticizers in various applications including biodegradable polymers food additives 50 . For food contact films various types of commercial CAPs such as TEC, TBC, ATEC, and ATBC were used for compostable polymers including PLA, 62,66–75 PHAs, 31,68,76–81 cellulose acetate, 82–84 PCL, 85 PBS, 66 and starch 86–88 …”
Section: Citrates Biobased Plasticizermentioning
confidence: 99%
See 1 more Smart Citation
“…CAPs derivatives are widely used as eco‐friendly plasticizers in various applications including biodegradable polymers food additives 50 . For food contact films various types of commercial CAPs such as TEC, TBC, ATEC, and ATBC were used for compostable polymers including PLA, 62,66–75 PHAs, 31,68,76–81 cellulose acetate, 82–84 PCL, 85 PBS, 66 and starch 86–88 …”
Section: Citrates Biobased Plasticizermentioning
confidence: 99%
“…However, the highest performance was recorded at plasticizers concentration of 30 wt%. Gálvez et al 71 reported a reduction in storage module and loss modulus in PLA as ATBC content increased. It can be concluded that at least 20 wt% of CAPs are needed to increase ductility and improve flowability of PLA.…”
Section: Citrates Biobased Plasticizermentioning
confidence: 99%
“…Nowadays, there is growing interest in biobased materials, especially for food packaging applications, to substitute the currently used petrochemical-based polymers. Among them, polylactic acid (PLA) has gained interest, because it can be synthesized from natural resources [3]. PLA can be used for single-use items that are used at room temperature, e.g., plastic utensils, cold-drink cups, thermoformed lunch boxes which are not reusable plasticware, plastic films, or, and rubber toughened for frozen applications [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The typical band of the asymmetric stretching of C-O in the ester group appeared at 1182 cm −1 , and in the TPS and PLA blends presented a greater intensity for samples containing oleic acid [29]. Ultimately, in the fingerprint region, two bands at 868 and 755 cm −1 were related to the C-C stretch vibration that corresponded to the amorphous and crystalline phase of PLA, respectively [21].…”
Section: Ir Analysismentioning
confidence: 95%
“…The range of plasticizers that contribute to this problem continues to expand. The aforementioned characteristics enable TPS and PLA to be considered as candidates for developing new biopolymers from this blend [21,22]. However, these components show low compatibility due to the hydrophilic nature of starch and the hydrophobic nature of PLA.…”
Section: Introductionmentioning
confidence: 99%